Microsomal triglyceride transfer protein -493T variant reduces IDL plus LDL apoB production and the plasma concentration of large LDL particles - Lundahl, Bjorn; Skoglund-Andersson, Camilla; Caslake, Muriel; Bedford, Dorothy; Stewart, Philip; Hamsten, Anders; Packard, Christopher J; Karpe, Fredrik (American journal of physiology: endocrinology and metabolism, 2006)
1 Atherosclerosis Research Unit, King Gustaf V Research Institute, Department of Medicine, Karolinska Institute, Karolinska Hospital, Stockholm, Sweden 2 Department of Pathological Biochemistry, University of Glasgow, Royal Infirmary, Glasgow 3 Oxford Centre for Diabetes, Endocrinology and Metabolism, Nuffield Department of Clinical Medicine, University of Oxford, Churchill Hospital, Oxford, United Kingdom Submitted 12 August 2005 ; accepted in final form 14 November 2005 The microsomal triglyceride transfer protein (MTP) is essential for the synthesis and secretion of apolipoprotein B (apoB)-containing lipoproteins. We investigated the role the MTP 493G/T gene polymorphism in determining the apoB-100 secretion pattern and LDL heterogeneity in healthy human subjects. Groups of carriers of the T and the G variants ( n = 6 each) were recruited from a cohort of healthy 50-yr-old men. Kinetic studies were performed by endogenous [ 2 H 3 ]leucine labeling of apoB and subsequent quantification of the stable isotope incorporation. apoB production rates, metabolic conversions, and eliminations were calculated by multicompartmental modeling (SAAM-II). LDL subfraction distribution was analyzed in the entire cohort ( n = 377). Carriers of the MTP 493T allele had lower plasma LDL apoB and lower concentration of large LDL particles [LDL-I: 136 ± 57 (TT) vs. 175 ± 55 (GG) mg/l, P < 0.01]. Kinetic modeling suggested that MTP 493T homozygotes had a 60% lower direct production rate of intermediate-density lipoprotein (IDL) plus LDL compared with homozygotes for the G allele ( P < 0.05). No differences were seen in production rates of large and small VLDL, nor were there any differences in metabolic conversion or elimination rates of apoB between the genotype groups. This study shows that a polymorphism in the MTP gene affects the spectrum of endogenous apoB-containing lipoprotein particles produced in humans. Reduced direct production of LDL plus IDL appears to be related to lower plasma concentrations of large LDL particles. intermediate-density lipoprotein; low-density lipoprotein; apolipoprotein B; very-low-density lipoprotein secretion; lipidation; microsomal triglyceride transfer protein Address for reprint requests and other correspondence: F. Karpe, Oxford Centre for Diabetes, Endocrinology and Metabolism, Nuffield Department of Clinical Medicine, Univ. of Oxford, Churchill Hospital, OX3 7LJ Oxford, UK (e-mail: fredrik.karpeatocdem.ox.ac.uk )